Modeling and control of an HVAC system - Zhang, Xiang (2016)
Heating, ventilating and air conditioning (HVAC) system control has been carried out in several decades, and the research activities are still on-going with more concerns recently. It has been discovered that indoor static air pressure level has a non-negligible impact on human comfort level. Hence, regulating and maintaining the static air pressure of the building becomes an interesting and meaningful topic. One way to achieve this goal is through controlling the air handling units (AHU) component in the HVAC system. Static air pressure is closely related to the indoor space and supply air volume. For a fixed indoor space, static air pressure can be regulated by varying the supply air volume. There are several methods can be used to control the AHU, in this thesis, the classical PID controller is adopted to address this problem. Model of the AHU is derived using the empirical method. A PID controller following the IMC design method is designed to this model. The result of experimental test shows that controller is able to adjust the AHU so that the static air pressure is at the set level and maintain at there. The result also demonstrates that the modeling is accurate and the controller designed for the HVAC system is effective. This result inspires the thoughts of adding the ability to deliver desired air pressure as a new feature of the HVAC system. This thesis proposes a method to predict and to control the AHU performances, hence, improving the overall user experience. Future improvement can be done on systems integration, minimizing the side effects of the actions on other parts of the HVAC system.